Biotechnological Applications of Plant Proteolytic Enzymes (Springer International Publishing, 2018)
This book offers an overview of the diverse fields application of proteases (also termed proteolytic enzymes or proteinases), including food science and technology, pharmaceutical industries, and detergent manufacturing, reviewing the advances in the biotechnological application plant proteolytic enzymes over the last decade. In recent years, they have been the focus of renewed attention from the pharmaceutical and biotechnology industries, not only because of their activity on a wide variety of proteins but also because they are active over a range of temperatures and pHs. The main audience of this book are researchers working with plant proteases but also professionals from several industry segments such as food production and pharmaceutical companies.